New technologies in brain vascular pathology diagnostic and treatment: Proceedings of the Conference of Neurosurgeons of Ukraine "New Technologies in Neurosurgery", Uzhgorod (Ukraine), April 26-28, 2006 - —, — (Ukrainian Neurosurgical Journal, 2006)
No abstract.